(3GdQO Ydi GdfMGIs - (3GHf eVGA , CMeO Hf YHO GdQMef Hf eMeO Hf YejQ GddNej GdbQWHj, CHh GdYHGS,J (B592 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEfg Medfj Ydi gPG GdecJhH bhd GdQShd Udi Gddg Ydjg hSde GdOjf GdfUjMI hYdi GdfGXQ aj gPG GdcJGH s
(3BNQgG (B:s
(3hHYVge HGdaGYd hHYVge HGdaYd hGdaGYd eYkG, hYdi GdLedI ajeG dG jajO fWbkG ced hGdMeO ddg s
(3HgG CKQ WeS dHYV GdCdaGX hGdYHGQGJ ef CKQ GdCQVIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B268s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B127 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B839s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdfMhs